Not appropriate dinner table conversation? Talking to children about meat production. (1st May 2016) - Bray, Heather J.; Zambrano, Sofia C.; Chur-Hansen, Anna; Ankeny, Rachel A.
Abstract: Although Australians on average consume large quantities of meat, their attitudes to farm animal welfare are poorly understood. We know little about how farm animal production is discussed in Australian households or how children learn about the origins of meat. This study consisted of an online survey completed by 225 primary carers throughout Australia recruited through social media. Findings include that conversations about the origin of meat were generally stimulated by meal preparation within the home rather than visits to agricultural shows or similar activities. Parents preferred to initiate conversations with children about meat production before they were 5 years of age. Urban parents were more likely than rural parents to reveal that they were conflicted about eating meat and would be more empathetic to children who chose to stop eating meat. Rural parents were more likely than urban parents to feel that children should eat what they are given and that talking about meat is not a major issue. Both groups felt that it was important that children should know where their food comes from. The findings of this study suggest that parental attitudes to meat production and consumption influence conversations about meat origins with children.